HVAD Waveform Analysis as a Noninvasive Marker of Pulmonary Capillary Wedge Pressure: A First Step Toward the Development of a Smart Left Ventricular Assist Device Pump. Issue 1 (January 2018) - Grinstein, Jonathan; Rodgers, Daniel; Kalantari, Sara; Sayer, Gabriel; Kim, Gene H.; Sarswat, Nitasha; Adatya, Sirtaz; Ota, Takeyoshi; Jeevanandam, Valluvan; Burkhoff, Daniel; Uriel, Nir
Abstract : Flow waveforms are an important feature of the HVAD left ventricular assist device (LVAD) that provides information about HVAD function and patient hemodynamics. We assessed the properties of one specific aspect of the waveform, the slope of the ventricular filling phase (VFP), and its correlation with pulmonary capillary wedge pressure (PCWP). A total of 101 screenshots from the HVAD monitor and simultaneous hemodynamic measurements were obtained simultaneously during sequential stages of invasive hemodynamic ramp studies. Each screenshot was digitized (IGOR Pro, WaveMetrics Inc., Oswego, OR) and properties of the flow waveforms including instantaneous flow and rate of change of flow were analyzed. Ventricular filling phase slope (VFPS) was calculated for each screenshot and correlated to PCWP. Ventricular filling phase slope was significantly higher in patients with PCWP ≥ 18 mm Hg than in patients with PCWP < 18 mm Hg [6.25 (5.84–7.37) L/min/s vs. 3.27 (2.00–4.69) L/min/s, p ⩽ 0.0001]. A VFPS threshold of 5.8 L/min/s predicted a PCWP ≥ 18 mm Hg with a sensitivity of 87% and specificity of 95% (AUC 0.95). Ventricular filling phase slope of the HVAD flow waveform is a novel noninvasive parameter that correlates with PCWP and can discriminate elevated versus normal or low PCWP. Automated reporting of this parameter may help clinical assessment and management of patients supported by an HVAD and may serve as the basis of a smart LVAD pump that can adapt in response to changes in a patient's physiology.